STUDI NUMERIK KINERJA PENDINGIN COOLANT HYBRID-NANOFLUID AL2O3-TIO2 PADA RADIATOR - Hidayat, Najmul; Sudarmadji, Sudarmadji (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Coolant in automotive engine cooling systems generally uses coolant with a minimum ethylene2 glycol mixture of 30 percent. Currently, the use of nanoparticles can be mixed in basic coolant between fluid and nanoparticles that have better thermal physical properties than pure coolant. The purpose of this study was to compare the results of CFD to tests on the effect of concentration, discharge and inlet temperature of Hybrid Nanofluid Al2O3 TiO2 to temperature distribution, pressure and radiator performance. The method used in this research is CFD simulation. The data taken in this study is the rate of heat transfer in the cooling fluid of pure radiator coolant and radiator coolant plus Al2O3 TiO2 hybrid nanoparticles (hybrid nanofluid radiator coolant) with a mass percentage of nanoparticle hybrid mixture of 0.25, 0.30, 0.35 percent. Variations in the amount of fluid flow with a liter/ minute discharge (LPM) of 20, 24 ,28, and using variations in the amount of radiator fluid inlet temperature (Tin), namely 70, 80, 90 Celsius which will be simulated by ANSYS FLUENT software.